Partially-parallel irregular LDPC decoder based on improved message passing schedule - Xing Li; Shimizu, K.; Zhen Qiu; Ikenaga, T.; Goto, S. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
In this paper, we propose a new efficient message-passing schedule for irregular LPDC code. Our approach is based on the schedule designed for regular LDPC code. We have modified the original schedule for regular LDPC code and improved it particularly for the irregular LDPC coder realization. The experimental results show that our method could achieve better performance than conventional one, and improve the converging rate as well.